1990
DOI: 10.1017/s0950268800047956
|View full text |Cite
|
Sign up to set email alerts
|

Faecal contamination of water and fingertip-rinses as a method for evaluating the effect of low-cost water supply and sanitation activities on faeco-oral disease transmission. I. A case study in rural north-east Thailand

Abstract: Faecal contamination of water and fingertip-rinses as a method for evaluating the effect of low-cost water supply and sanitation activities on faeco-oral disease transmission. I. A case study in rural north-east Thailand J. V. PINFOLD Department of Civil Engineering, University of Leeds, Leeds LS2 9JT, England (Accepted 25 May 1990) SUMMARYMost villagers in north-east Thailand carry water to their homes and store it in separate containers depending on its subsequent use. In one village, information on water us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
4

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 13 publications
3
37
0
4
Order By: Relevance
“…Ambient humidity has been shown to be correlated with fingertip contamination. 8 Among persons who do wash hands with soap, the duration of wash time with soap and the volume of soap used for handwashing may also impact the level of hand contamination detected. 17 Of course, factors related to the sample collection and the microbiological tests themselves, including the inconsistency in rigor and technique of rinsing the respondent's hands during sample collection, the methodology used to count the number of organisms or colonies of organisms, and the consistency in the media and other materials, may be responsible for variability in the levels of hand contamination detected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ambient humidity has been shown to be correlated with fingertip contamination. 8 Among persons who do wash hands with soap, the duration of wash time with soap and the volume of soap used for handwashing may also impact the level of hand contamination detected. 17 Of course, factors related to the sample collection and the microbiological tests themselves, including the inconsistency in rigor and technique of rinsing the respondent's hands during sample collection, the methodology used to count the number of organisms or colonies of organisms, and the consistency in the media and other materials, may be responsible for variability in the levels of hand contamination detected.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Hand-contamination measurement seems promising as a proxy method for measuring handwashing behavior, because persons specifically instructed to wash hands with a cleansing agent have been shown to have substantially fewer fecal bacteria contaminating their hands compared with people who have not washed hands with a cleansing agent. [6][7][8] Some studies have shown a correlation between reduced hand contamination and reduced diarrhea risk. [9][10][11] However, measured hand contamination can vary based on a number of factors, including the type of sampling and the microbial quantitation methods used, 10 the subject's skin characteristics, 12 humidity, 8 and hygiene behaviors temporally related to the hand-contamination measurement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outro aspecto observado é a imersão desses utensílios com as próprias mãos, o que compromete a qualidade da água de consumo, pois a parte inferior das unhas pode albergar microrganismos patogênicos. Há relatos da presença de bactérias, como Escherichia coli ETEC (enterotoxicogênica), e evidências de contaminação fecal nas unhas de donas-de-casa (Pinfold 1990;Trevett e col., 2005).…”
Section: Fatores De Impacto Na Qualidade Sanitária Da áGua Coletada unclassified
“…[25][26][27][28] These and other previous studies have used the quantitative measurement of fecal indicator bacteria (FIB), such as fecal coliforms, fecal streptococci, and E. coli , on hands to evaluate hand hygiene. [29][30][31] These organisms are not pathogens, but are used to indicate fecal contamination. Further work is needed to determine the relationship between the presence of these indicators on hands, hand hygiene behavior, and health.…”
Section: Introductionmentioning
confidence: 99%